2022
DOI: 10.1136/bmjopen-2022-063835
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal corticosteroid use for prevention or treatment of bronchopulmonary dysplasia in England and Wales 2012–2019: a retrospective population cohort study

Abstract: ObjectiveDescribe the population of babies who do and do not receive postnatal corticosteroids for prevention or treatment of bronchopulmonary dysplasia (BPD).DesignRetrospective cohort study using data held in the National Neonatal Research Database.SettingNational Health Service neonatal units in England and Wales.PatientsBabies born less than 32 weeks gestation and admitted to neonatal units from 1 January 2012 to 31 December 2019.Main outcomesProportion of babies given postnatal corticosteroid; type of cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 36 publications
2
20
3
Order By: Relevance
“…These data are different from those of the EPICE cohort, showing exposure rates of 35.8% ( Shaffer et al, 2019 ), and from those reported in some US studies (up to 38% in extremely preterm infants) ( Puia-Dumitrescu et al, 2022 ). In the retrospective study of the UK Neonatal Collaborative ( Yao et al, 2022 ), the rate of PC use for the prevention or treatment of BPD was 8% in 62,019 infants born at less than 32 weeks of gestation, thus substantially lower compared to our cohort. However, despite an overlapping between the study periods, it is difficult to compare these populations, as in the UK cohort dexamethasone was predominantly used, followed by late hydrocortisone.…”
Section: Discussioncontrasting
confidence: 56%
“…These data are different from those of the EPICE cohort, showing exposure rates of 35.8% ( Shaffer et al, 2019 ), and from those reported in some US studies (up to 38% in extremely preterm infants) ( Puia-Dumitrescu et al, 2022 ). In the retrospective study of the UK Neonatal Collaborative ( Yao et al, 2022 ), the rate of PC use for the prevention or treatment of BPD was 8% in 62,019 infants born at less than 32 weeks of gestation, thus substantially lower compared to our cohort. However, despite an overlapping between the study periods, it is difficult to compare these populations, as in the UK cohort dexamethasone was predominantly used, followed by late hydrocortisone.…”
Section: Discussioncontrasting
confidence: 56%
“…Another study found no variation in the combined outcomes of death at PMA 36 weeks or occurrence of BPD, PMA at 28 days, and death at PMA 36 weeks between the allocation groups. For the incidence of BPD at 28 days PMA and 36 weeks PMA, newborns with delayed start (>21 days PMA) were more numerous than those with a moderately early start (8–21 days PMA) 8 . There are no neurodevelopmental findings for infants whose medications were started at different times.…”
Section: Applications Of Systemic Glucocorticoidsmentioning
confidence: 93%
“…For the incidence of BPD at 28 days PMA and 36 weeks PMA, newborns with delayed start (>21 days PMA) were more numerous than those with a moderately early start (8-21 days PMA). 8 There are no neurodevelopmental findings for infants whose medications were started at different times.…”
Section: Different Sg Regimensmentioning
confidence: 99%
See 2 more Smart Citations